Legal Capital and Finances of the Company - Veress , Emőd (Joint Stock and Limited Liability Companies in East Central Europe, 2025)
References:Angheni, S. (2013) Drept comercial. Profesionişti-comercianţi. Bucureşti: C.H. Beck.Barbić, J. (2010) Pravo društava: Društva kapitala, Svezak I. i II. Zagreb: Organizator.Bezzenberger, T. (2005) Das Kapital der Aktiengesellschaft. Köln: Otto Schmidt.Čech, P., Skálová, J. (2014) ‘Zálohy společníkům na podíly na zisku v kapitálových společnostech – právní a účetní pohled’, Obchodněpravni revue, 6(9), pp. 241–250.Černá, S., Štenglová, I., Pelikánová, I. et al. (2021) Pravo obchodnich korporaci, 2nd edn. Praha: Wolters Kluwer.Cerovac, M. (2004) Rječnik pojmova prava i politike tržišnog natjecanja i srodnih pojmova. Zagreb: Hrvatska udruga za zaštitu tržišnog natjecanja.David, S. (2014) in Cărpenaru, St.D., Piperea, Gh., David, S., (eds.) Legea societăților. Comentariu pe articole, 5th edn. București: C.H. Beck.Dolný, J., in Patakyová, M., Ďurica, M., Husár, J. et al. (2021) Aplikovane pravo obchodnych spoločnosti a družstva – ťažiskove inštituty. Bratislava: Wolters Kluwer SR.Eichlerová, K. (2014) ‘Záloha na podíl na zisku v kapitálových společnostech’, Bulletin advokacie, (11), [Online]. Available at: http://www.bulletin-advokacie.cz/zalohana-podil-na-zisku-v-kapitalovych-spolecnostech (Accessed: 10 October 2025).Flídr, J. (2018) ‘Zákaz vracení předmětu vkladu jako účinný nástroj ochrany věřitelů kapitálové společnosti’, Obchodněpravni revue, 10(9), pp. 241–247.Gerner-Beuerle, C., Schillig, M. (2019) Comparative Company Law. Oxford: Oxford University Press.Hejnar, J., Micherda, B. (2011) Kapitały własne, aktywa pieniężne i rozrachunki według polskiego prawa bilansowego. Warszawa: Stowarzyszenie Księgowych w Polsce.Hennrichs, J. (2009) ‘Kapitalschutz bei GmbH, UG und SPE’, Neue Zeitschrift fur Gesellschaftsrecht, 2009/28, pp. 290–298.Höfer, C. (2016) ‘Flex-GmbH – eine solvenzorientierte Schwester-Rechtsform für die GmbH?’, Zeitschrift fur Gesellschaft-, Unternehmens- und Steuerrecht der GmbH und GmbH & Co. KG, 2016/8, pp. 123–131.Ivanjko, Š., Kocbek, M., Prelič, S. (2009) Korporacijsko pravo. Ljubljana: GV Založba.Janošek, V. (2015) ‘Vyloučení (většinového) společníka ze společnosti s ručením omezeným rozhodnutím valné hromady’, Obchodněpravni revue, 7(5), pp. 134–142.Jovanović, N., Radović, V., Radović, M. (2021) Kompanijsko pravo – Pravo privrednih društava, 2nd edn. Beograd: Pravni fakultet u Beogradu, Centar za izdavaštvo i informisanje.Kidyba, A. (2023) Kodeks społek handlowych. Komentarz. Tom I i II, 18th edn. Warszawa: Wolters Kluwer.Komarnicki, I. (2004) Prawo akcjonariusza do udziału w zysku. Warszawa: Wydawnictwo C.H. Beck.Kotowicz, M. (2014) ‘Kapitał zakładowy w spółce z ograniczoną odpowiedzialnością– skuteczny instrument ochrony wierzycieli?’, Adam Mickiewicz University Law Review, 2014/3, pp. 25–35.Lasák, J., Dědič, J., Pokorná, J., Čáp, Z. et al. (2021) Zakon o obchodnich korporacich. Komentař, 2nd edn. Praha: Wolters Kluwer ČR.Lokajíček, J. (2016) Prolomeni majetkove samostatnosti kapitalovych společnosti. Praha: C. H. Beck.Marjanski, V. (2020) ‘Raspodela dobiti članovima društva sa ograničenom odgovornošću i razlika u odnosu na druge isplate korporativno-pravnog karaktera’, Zbornik radova Pravnog fakulteta u Novom Sadu, 54(1), pp. 215–243 [Online]. Available at: https://doi.org/10.5937/zrpfns54-26336 (Accessed: 10 October 2025).Nędzyński, S. (2021) ‘Prosta spółka akcyjna jako remedium na problemy polskich start-upów’, Zeszyt Prawniczy UAM, 2021/11, pp. 233–248 [Online]. Available at: https://doi.org/10.14746/zpuam.2021.11.15 (Accessed: 10 October 2025).Ovečková, O. et al. (2022) Obchodny zakonnik. Veľky komentar, vol. I, 2nd edn. Bratislava: Wolters Kluwer SR.Patakyová, M. et al. (2022) Obchodny zakonnik. Komentar, 1st edn. Bratislava: C.H. Beck.Piperea, Gh. (2014) in Cărpenaru, St.D., Piperea, Gh., David, S., (eds.) Legea societăților. Comentariu pe articole, 5th edn. București: C.H. Beck.Sárközy, T. (2001) A magyar tarsasagi jog Europaban. Budapest: HVGOrac.Scholz, F. (ed.) (2022) Kommentar zum GmbHG, 13th edn. Köln: Otto Schmidt.Siemiątkowski, T., Potrzeszcz, R. (eds.) (2001) Komentarz do Kodeksu społek handlowych. Warszawa: LexisNexis Polska.Širola, N. (2011) ‘Odgovornost članova društva s ograničenom odgovornošću za nedopušten zahvat u imovinu društva’, Zbornik Pravnog fakulteta Sveučilišta uZagrebu, 61(5), pp. 1443–1471 [Online]. Available at: https://hrcak.srce.hr/74553 (Accessed: 25 August 2024).Spoz, A. (2017) ‘Kapitał zakładowy w sprawozdawczości finansowej spółek z ograniczoną odpowiedzialnością’, Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu, 484, pp. 197–206 [Online]. Available at: https://doi.org/10.15611/pn.2017.484.16 (Accessed: 10 October 2025).Stanciu, D. C. (2014) Tratat de drept comercial. Bucureşti: Universul Juridic.Štenglová, I., Dědič, J., Lasák, J., Pihera, V., Lála, D., Josková, L. (2023) Akciove společnosti, 1st edn. Praha: C. H. Beck.Štenglová, I., Havel, B., Cileček, F., Kuhn, P., Šuk, P. (2020) Zakon o obchodnich korporacich. Komentař, 3rd edn. Praha: C. H. Beck.Šuleková, Ž. (2016) ‘Jednoduchá spoločnosť na akcie – nová forma obchodnej spoločnosti’, Sukromne pravo, 2(6), pp. 2–10.Szajkowski, A., Tarska, M. (2005) Prawo społek handlowych, 5th edn. Warszawa: C.H. Beck.Veličković, J. (2019a) ‘Ograničenja plaćanja članovima društva kapitala: opšti pogled’, Pravo i privreda, 61(2), pp. 294–315.Veress, E. (2024) ‘A társasági jog elmélete és a társaságok általános jellemzői’ inFegyveresi, Zs. (ed.) Roman tarsasagi jog, 3rd edn. Cluj-Napoca: Forum Iuris.Weiss, I. (1994) ‘Podwyższenie kapitału zakładowego i dopłaty w spółce z ograniczoną odpowiedzialnością’, Przegląd Prawa Handlowego, 12, pp. 1–8.Winnefeld, R. (2015) Bilanz-Handbuch, 5th edn. München: C.H. Beck